Pengaruh Kecerdasan Emosional, Minat Belajar, Dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi Dasar (Studi Kasus Mahasiswa Akuntansi Politeknik Negeri Padang) - Sukartini; Tesa Sofyra; Yossi Septriani (Politeknik Negeri Padang, 2023)
This study aims to determine the effect of emotional intelligence, interest in learning, and learning behavior on the level of understanding of basic accounting. This research is a quantitative research. The method of data collection is using a questionnaire instrument which is distributed online via google form. The population of this research is the Accounting students of the Padang State Polytechnic class of 2018, 2019, and 2020 for the Accounting DIV study program and the 2019 and 2020 batches for the Accounting DIII study program totaling 367 people. The research sample amounted to 159 people. Samples were taken using a selection method with certain criteria. Analysis of the data used is multiple linear regression analysis using SPSS version 23. Based on the results of data processing, it can be concluded that partially emotional intelligence has no significant effect on the level of understanding of basic accounting, interest in learning has a significant effect on the level of understanding of basic accounting and learning behavior has an effect significant to the level of understanding of basic accounting, while simultaneously emotional intelligence, interest in learning, and learning behavior affect the level of understanding of basic accounting.